The Power of the Presidency in EU Council Decision-making - Schalk, Jelmer; Torenvlied, René; Weesie, Jeroen; Stokman, Frans (2007)
Abstract: Research on the presidency of the EU shows mixed results. Although most scholars agree that the EU presidency is not able to advance its domestic interests in the European forum, Tallberg (2006) provides evidence for presidency effects. In the present paper, we empirically estimate presidency-based power in the Council of the European Union on the DEU data — a large-scale data set containing EU policy issues from various policy areas. We show that holding the presidency does significantly and positively contribute to the bargaining power of member states, but only in the final stages of decision-making